2018
DOI: 10.1089/neu.2017.5262
|View full text |Cite
|
Sign up to set email alerts
|

Mild Jugular Compression Collar Ameliorated Changes in Brain Activation of Working Memory after One Soccer Season in Female High School Athletes

Abstract: Recent neuroimaging studies have suggested that repetitive subconcussive head impacts, even after only one sport season, may lead to pre- to post-season structural and functional alterations in male high school football athletes. However, data on female athletes are limited. In the current investigation, we aimed to (1) assess the longitudinal pre- to post-season changes in functional MRI (fMRI) of working memory and working memory performance, (2) quantify the association between the pre- to post-season chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Resting‐state fMRI studies conducted in American high school football players over one or two football seasons, whether they sustained concussions, showed significant changes in fMRI, including a prolonged alteration in DMN, suggesting possible accrued RHSI‐related damage (Abbas et al., 2015; Breedlove et al., 2012). Only one fMRI study was conducted in female high school soccer players: significant pre‐ to postseason changes in fMRI brain activation were demonstrated when performing a working memory task (Yuan et al., 2018). No studies have assessed the relationship between soccer‐related RHSI exposure in trained male players and their brain function at rest.…”
Section: Introductionmentioning
confidence: 99%
“…Resting‐state fMRI studies conducted in American high school football players over one or two football seasons, whether they sustained concussions, showed significant changes in fMRI, including a prolonged alteration in DMN, suggesting possible accrued RHSI‐related damage (Abbas et al., 2015; Breedlove et al., 2012). Only one fMRI study was conducted in female high school soccer players: significant pre‐ to postseason changes in fMRI brain activation were demonstrated when performing a working memory task (Yuan et al., 2018). No studies have assessed the relationship between soccer‐related RHSI exposure in trained male players and their brain function at rest.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of venous dilation is purported to be less than a human's natural physiologic response to a Valsalva maneuver, sneeze, or cough (Myer, Yuan, Barber Foss, Thomas, et al., 2016). Previous prospective longitudinal clinical trials have not reported any harm or injury related to collar wearing (Bonnette et al., 2018; Dudley et al, 2020; Myer et al, 2018; Myer, Yuan, Barber Foss, Smith, et al., 2016; Myer, Yuan, Barber Foss, Thomas, et al., 2016; Yuan, Barber Foss, et al., 2018; Yuan, Dudley, et al., 2018; Yuan et al., 2017), nor were any reported in the present study.…”
Section: Methodsmentioning
confidence: 98%
“…Although still an indirect measure of histopathology, DTI is capable of quantifying the characteristics of diffusion and anisotropic properties of water molecules within cerebral white matter microstructure (American College of Radiology, 2019; Soares, Marques, Alves, & Sousa, 2013). The technique has been used extensively to characterize white matter alterations in response to neurologic insult resulting from head trauma (Aoki, Inokuchi, Gunshin, Yahagi, & Suwa, 2012; Bahrami et al., 2016; Bazarian, Zhu, Blyth, Borrino, & Zhong, 2012; Bazarian et al., 2014; Chamard & Lichtenstein, 2018; Chun et al., 2015; Davenport et al., 2014; Eierud et al., 2014; Gajawelli et al., 2013; Inglese et al., 2005; Kuzminski et al., 2018; Marchi et al., 2013; Mayinger et al., 2018; McAllister et al., 2014; Merchant‐Borna et al., 2016; Mustafi et al., 2018; Myer et al, 2018; Myer, Yuan, Barber Foss, Smith, et al., 2016; Myer, Yuan, Barber Foss, Thomas, et al., 2016; Newcombe et al., 2007; Slobounov et al., 2017; Sollmann et al., 2018; Urban et al., 2013; Wallace, Mathias, & Ward, 2018; Yuan, Barber Foss, et al., 2018; Yuan, Dudley, et al., 2018). With respect to American football, a recent systematic review of prospective studies revealed that longitudinal changes in DTI metrics—specifically fractional anisotropy (FA) and mean/axial/radial diffusivity (MD, AD, RD)—were associated with high‐school athletes' cumulative exposure (quantity and magnitude) to head impacts experienced throughout their competitive season (Schneider et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations